GAMBARAN KELENGKAPAN RESEP SECARA ADMINISTRATIF DAN FARMASETIK DI APOTEK X - Devi A, Stephanie; Sriyanti, Titis (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Prescription screening is important to minimize medication errors and prevent adverse patient events. The prescription service flow involves steps of administrative handling, pharmaceutical, and clinical screening. This study aimed to assess the completeness of prescriptions determining the proportion of prescriptions that are complete in terms of administrative and pharmaceutical aspects at the Kebelenan Pharmacy. It was a descriptive study, describing it systematically, using a cross-sectional research design—the prospective method used for data collection. The study used 80 prescriptions entered at the X Pharmacy in February 2023. The research results were complete administration of prescriptions written by doctors, namely doctor's name (100%), doctor's license number (100%), doctor's address (100%), telephone number (100%), prescription date (100%), doctor's initials (100%), and patient's name (100%). As for the completeness of the prescription, the patient's address (76%), gender (64%), age (49%), and body weight (3.7%) were lacking. Then for the completeness of the recipe that does not exist, namely height (0%). While the pharmaceutical equipment written by the doctor is the drug’s name (100%), amount of drug (100%), instructions for use (100%), and stability (100%). While the completeness of the recipe still needs dosage form (84%) and dosage strength (39%). Then for the results of the completeness of the recipe, there is no drug mixing (0%). Conclusion: several administrative and pharmaceutical completeness aspects still need to comply with the stipulated regulations.